2022
DOI: 10.1007/s12310-021-09491-1
|View full text |Cite
|
Sign up to set email alerts
|

Teacher and School Characteristics Associated with the Identification and Referral of Adolescent Depression and Oppositional Defiant Disorders by U.S. Teachers

Abstract: Teachers contribute to the process of identifying and referring students for mental health services, however, relatively little is known about how they make those decisions and how decision-making differs across school contexts. This study used a vignette-based method to investigate individual and school contextual factors associated with the likelihood that teachers identify and refer students for mental health services. Teachers were recruited from public middle and high schools across the U.S. using a strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Obeid et al (2015) and van‘t Hof et al (2020) confirmed the absence of a relationship between stigma and knowledge, suggesting that stigma and beliefs must be tackled directly, rather than being addressed by increasing knowledge. However, Green et al (2022) highlighted that a single training approach might not be equally practical for different school and cultural contexts. For instance, in the United States, knowledge of autism is higher and stigma towards autism is lower than in Lebanon (Obeid et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Obeid et al (2015) and van‘t Hof et al (2020) confirmed the absence of a relationship between stigma and knowledge, suggesting that stigma and beliefs must be tackled directly, rather than being addressed by increasing knowledge. However, Green et al (2022) highlighted that a single training approach might not be equally practical for different school and cultural contexts. For instance, in the United States, knowledge of autism is higher and stigma towards autism is lower than in Lebanon (Obeid et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Participants were middle and high school teachers recruited from a sample of schools across the United States (Green et al, 2022). To identify teachers, we downloaded a list of all U.S. public middle and high schools from the Department of Education website and stratified by region of the country and urbanicity.…”
Section: Participantsmentioning
confidence: 99%
“…These final vignettes were 100-130 words with symptom descriptions based on ODD criteria from the Diagnostic and Statistical Manual of Mental Disorders-Fifth Edition (DSM-5; American Psychiatric Association [APA], 2013). Subsequently, we validated the vignettes using data from 14 clinical and research experts in child and adolescent mental health and data from 100 school psychologists recruited from the National Association of School Psychologists mailing list (Green et al, 2022). This validation process was used to confirm that the "severe" vignettes reflected greater impairment than the "moderate" vignettes and that the vignettes were considered realistic.…”
Section: Vignette Measurementioning
confidence: 99%
See 1 more Smart Citation